2024
DOI: 10.1111/jvim.16990
|View full text |Cite
|
Sign up to set email alerts
|

Development of a requirement for exogenous insulin treatment in dogs with hyperglycemia

Angielee DiNinni,
Rebecka S. Hess

Abstract: BackgroundIt has been suggested that overt diabetes mellitus in dogs be defined based on a persistent fasting blood glucose concentration (BGC) >144 mg/dL.ObjectiveDetermine the number of dogs with randomly identified hyperglycemia without insulin‐treated diabetes mellitus (ITDM) that later develop a need for exogenous insulin treatment.AnimalsA total of 1318 dogs examined at a university teaching hospital without ITDM and with randomly identified hyperglycemia.MethodsRetrospective longitudinal study. Hyper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…To date, no published research has applied these new concepts to investigate actual PRDM incidence in bitches during diestrus, pregnancy, or other P4-related conditions. However, a recent study found that only 3.5% of the dogs identified with random hyperglycemia between 126 and 200 mg/dL needed insulin treatment somewhere in the future [ 60 ], and none of those cases were in diestrus or pregnant at the time hyperglycemia was first documented. In women, GDM prevalence varies from 1 to 14% according to the studied population [ 57 , 58 , 59 ], and genetics [ 61 ], ethnicity [ 62 ], and overweight status [ 63 ] are known risk factors.…”
Section: Estrus Cycle Effects On Insulin Sensitivitymentioning
confidence: 99%
“…To date, no published research has applied these new concepts to investigate actual PRDM incidence in bitches during diestrus, pregnancy, or other P4-related conditions. However, a recent study found that only 3.5% of the dogs identified with random hyperglycemia between 126 and 200 mg/dL needed insulin treatment somewhere in the future [ 60 ], and none of those cases were in diestrus or pregnant at the time hyperglycemia was first documented. In women, GDM prevalence varies from 1 to 14% according to the studied population [ 57 , 58 , 59 ], and genetics [ 61 ], ethnicity [ 62 ], and overweight status [ 63 ] are known risk factors.…”
Section: Estrus Cycle Effects On Insulin Sensitivitymentioning
confidence: 99%